PENGARUH SOSIALISASI PERPAJAKAN TERHADAP NIAT UNTUK MEMATUHI KEWAJIBAN PERPAJAKAN CALON WAJIB PAJAK DENGAN KESADARAN PAJAK SEBAGAI VARIABEL INTERVENING - Sahrul Ramadhan; Dewi Kusuma Wardani; Anita Primastiwi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2021)
This study aims to reveal whether the socialization of taxation to high school students in Yogyakarta has an effect on their intention to comply with taxes through tax awareness. This research data uses direct / primary data. The sampling method is convenience sampling. The data analysis technique is path analysis with the socialization of taxation being the independent variable and the intention to comply with taxes as the dependent variable, and tax awareness being the intervening variable. The results of the analysis conclude that tax socialization has a positive effect on tax awareness and tax compliance intentions, tax awareness also has a positive effect on tax compliance intentions, and tax socialization also has a positive effect on tax compliance intentions through tax awareness. The implication of this research proves that the socialization of taxation is one of the elements that has an important role in the growth of tax compliance intentions within prospective taxpayers.